Cell-type specific cis-regulatory networks - Polychronidou, Maria; Lohmann, Ingrid (Fly, 2013)
Hox proteins are a prominent class of transcription factors that specify cell and tissue identities in animal embryos. In sharp contrast to tissue-specifically expressed transcription factors, which coordinate regulatory pathways leading to the differentiation of a selected tissue, Hox proteins are active in many different cell types but are nonetheless able to differentially regulate gene expression in a context-dependent manner. This particular feature makes Hox proteins ideal candidates for elucidating the mechanisms employed by transcription factors to achieve tissue-specific functions in multi-cellular organisms. Here we discuss how the recent genome-wide identification and characterization of Hox cis-regulatory elements has provided insight concerning the molecular mechanisms underlying the high spatiotemporal specificity of Hox proteins. In particular, it was shown that Hox transcriptional outputs depend on the cell-type specific interplay of the different Hox proteins with co-regulatory factors as well as with epigenetic modifiers. Based on these observations it becomes clear that cell-type specific approaches are required for dissecting the tissue-specific Hox regulatory code. Identification and comparative analysis of Hox cis-regulatory elements driving target gene expression in different cell types in combination with analyses on how cofactors, epigenetic modifiers and protein-protein interactions mediate context-dependent Hox function will elucidate the mechanistic basis of tissue-specific gene regulation.